Promotional tools effectiveness: a study case of zakat at Johor / Norashikin Mustaffa - Mustaffa, Norashikin (Faculty of Business and Management, 2009)
This research is all about a study on promotional effectiveness of Zakat Harta at Majlis Agama Islam Negeri Johor (MAIJ). Factors such as promotional effectiveness have been identified in order to investigate whether or not these factors have a relationship with MAIJ existing promotion activities. The main objective of this research is to study the level of promotional effectiveness towards the promotion activities that has been provided by MAIJ to zakat Harta payer. Furthermore, it will identify the weaknesses of the existing promotion and make any development to improve it. The survey is conducted at MAIJ involve all staff. The sample size of this study is 57 MAIJ staff. Respondents are required to answer the questionnaire that contain element that potentially have relationship with promotional effectiveness. Data are analyzed using statistical package of Social Science (SPSS). The data used frequency distribution such as measures of location is mean. Mean or average value, is the most commonly used measures of central tendency, with most of the response’s distribution around the mean. Standard error is calculated because it is to determine the reliability of the sample. The results show that in promotional effectiveness, there are many aspects need to be focused in order to increase payment of Zakat Harta.